Disclosing for sustainability: the need for a wider application of environmental reporting laws - Edirisinghe, A.A. (University of Jaffna, 2016)
Since 1980's there has been a common consensus around the world that the development shall not merely confined to the economic growth but shall take into account the environmental and social aspects as well. In order to attain this objective, it is important to ensure that the business enterprises are accountable towards the environment and its stakeholders. However, the legal framework in Sri Lanka which provides for environmental reporting is limited to a certain set of business entities by application. The main issue which is sought to be addressed in this research is the limited-obligation placed on the applicability of the environmental reporting laws in Sri Lanka based on the size of the enterprise. This research is aimed to prove that the application of environmental reporting laws shall not be based on the size of a particular business enterprise drawing evidence from the rubber industry in Sri Lanka. This research is conducted based on Sri Lanka Accounting and Auditing Standards Act No. 15 of 1995, Code of Best Practice on Corporate Governance in 2013, National Environmental Act No 47 of 1980 as amended and formal interviews as primary sources and journal articles, conference proceedings and commentaries as secondary sources. Conclusion and recommendations will be followed by the gathered and analysed data with special reference to rubber industry in Sri Lanka.
Keywords: Environmental reporting; Rubber industry; Sri lanka